Impacts of degree of milling on the appearance and aroma characteristics of raw rice. (30th October 2015) - Rodríguez‐Arzuaga, Mariana; Cho, Sungeun; Billiris, María A; Siebenmorgen, Terry; Seo, Han‐Seok
Abstract: BACKGROUND: Little has been reported about the sensory impact of degree of milling (DOM) on raw, uncooked rice. This study focuses on the effects of DOM, which was measured by surface lipid content (SLC), on appearance and aroma attributes of raw rice, as well as the appearance of cooked rice; greater DOM leads to lesser SLC levels. RESULTS: Milled‐rice samples with SLCs of 0.64, 0.59, 0.42 and 0.25%, as well as brown rice (2.27% total lipid content), were evaluated by trained panelists on three appearance‐ and five aroma‐related attributes of raw rice, as well as four appearance‐related attributes of the resultant cooked rice. All milled‐rice samples, varying in SLC level from 0.64% to 0.25%, differed from brown rice with respect to raw‐rice and cooked‐rice appearance and aroma attributes. A significant sensory difference among the four raw‐rice samples was present only in the degree of whiteness; however, such a difference was absent once the samples were cooked. When cooked, highly milled rice (0.25% SLC) was rated glossier than either lightly milled rice (0.64% SLC) or brown rice. CONCLUSION: The present study demonstrated that sensory impacts of DOM on raw rice were present between brown rice and milled‐rice samples, but not among the milled‐rice samples varying in SLC level from 0.64% to 0.25%. The overall findings indicate that consumers may not detect appearance‐ or aroma‐related differences among raw‐rice samples ranging in SLC from 0.64% to 0.25%. © 2015 Society of Chemical Industry